Effect of Mastery Learning Strategy on Achievement in English in Relation to Intelligence - Mehar, Dr. Ram (INDIAN EDUCATIONAL REVIEW, 2013)
The present study investigates the effect of mastery learning strategy on achievement in English in relation to intelligence. The sample was drawn of IXth class students taken from two different schools of Panchkula (Haryana), affiliated to CBSE, New Delhi. Instructional material based on mastery learning strategy were prepared and implemented to the experimental group after pre-testing. The gain scores were computed after post-test for all the students. General Mental Ability Test (1972) by Jalota was also administered. A 2 ×3 analysis of variance was used to arrive at the following conclusions: (i) Mastery learning strategy group was found to attain significantly higher achievement scores as compared to conventional group, (ii) Performance of students with different intelligence levels through mastery learning strategy was found significant, (iii) Significant interaction effect was found to exist between the two variables.